PERANCANGAN SISTEM INFORMASI PERENCANAAN PEMBANGUNAN DAERAH KABUPATEN KUBU RAYA - Ariza, Indradwita (Jurusan Informatika Universitas Tanjungpura, 2014)
Deliberation sub district development plan is one way to increase the impact of development. Results of deliberation sub district development planwill be discussed again in the unit forums then compiled and refined into a work plan. Planning Information Planning is an application development used to improve the performance deliberation sub district development plan and unit forums on Bappeda Kubu Raya and participant from various regions and unit forums. In practice often found several obstacles such as the absence so information systems can assist in the implementation of this activity. The author builds information systems development using the Technology Acceptance Model (tam) and Structural Equation Models (sem) in the design and establishment of web applications. This site will be operated by an employee and become operator of each district or unit forum. The operator will get an account from Bappeda Kubu Raya, then the operator of a sub district or unit forum can use the application to include the proposed activities of the sub district or unit forum. Operators who use these web applications can participate without having to meet in a room. Results can also be seen by web visitors.